Low-conductance intercellular coupling between mouse chromaffin cells in situ - Moser, Tobias (Blackwell Science Inc, 1998)
1. Patch-clamp experiments were used to compare membrane properties of mouse chromaffin cells in thin tissue slices and of isolated cells in primary culture. The mean membrane input resistance (R(in)) and membrane capacitance were 3.1 ± 0.5 GΩ and 9.1 ± 0.5 pF in situ and 9.9 ± 1.8 GΩ and 8.2 ± 0.2 pF in isolated cells. 2. Spike-like currents were observed on top of the calcium currents during depolarizations in thirty out of forty-nine cells in situ. They were not seen in isolated cells nor after addition of Cd(2+) (100 μm) and TTX (10 μm) to the perfusate of the slices. The mean R(in) of cells which displayed current spikes (2.3 ± 0.18 GΩ) was significantly smaller than that of cells lacking spikes (3.9 ± 0.25 GΩ). It is suggested that the current spikes represent intercellular currents which result from action potential firing in neighbouring cells during the depolarization of the patch-clamped cell. 3. Investigation of capacitative currents induced by square voltage pulses showed a slow component in twenty-four out of twenty-seven cells in situ. 4. It is concluded that a large fraction of mouse chromaffin cells in situ are electrically coupled. From the slow capacitative currents and the amplitude of the intercellular current spikes a junctional conductance between chromaffin cells of below 1 nS was deduced. 5. This junctional conductance appears to be too low to support spreading of electrical activity in cases where a single cell is stimulated by an action potential. However, the junctional conductance could allow longer depolarizations of one cell or simultaneous firing of several cells to trigger electrical activity in neighbouring cells.